Serum and urinary biomarkers in lupus nephritis: do suPAR and VEGF play a role? - Tamires Teixeira Piraciaba; Michelle Tiveron Passos Riguetti; Gianna Mastroianni Kirsztajn (Brazilian Journal of Nephrology)
Abstract Introduction: The extent, activity, and effects of renal involvement in systemic lupus erythematosus are conditions difficult to diagnose and a renal biopsy is usually required for such purpose. Non-invasive methods are then of high interest to better understand lupus nephritis (LN) features and prognosis. We have evaluated VEGF and suPAR levels as non-invasive biomarkers of disease activity in LN. Methods: This cross-sectional study enrolled patients with LN aged 18 years or older of both genders who were assisted at the Outpatient Clinic of Glomerular Diseases of the Division of Nephrology of the Federal University of São Paulo (UNIFESP). Clinical renal histopathological characteristics, routine laboratory test profiles, and serum and urinary suPAR and serum VEGF of patients with LN were evaluated. Results: The sample consisted of 51 patients with LN, most of them females (88.2%), white (51.0%) with a mean age of 36.1 years (18 to 65 years), and a median disease duration of 2.5 years (1 month to 32 years). A positive correlation of urinary suPAR with SLEDAI-2K scores and hematuria was found. No significant correlation was found between serum VEGF and serum and urinary suPAR and proteinuria, serum creatinine, and urinary protein/creatinine ratio. Conclusions: Serum suPAR and VEGF levels were not indicative of renal or general SLE activity, but our data suggest that urinary suPAR may be a useful biomarker of such conditions, as its levels have been shown to correlate with the presence of hematuria and with higher SLEDAI-2K scores.